ACTR-42. PI3K/mTOR PATHWAY ACTIVATION SELECTED PHASE II STUDY OF EVEROLIMUS (RAD001) WITH AND WITHOUT TEMOZOLOMIDE IN THE TREATMENT OF ADULT PATIENTS WITH SUPRATENTORIAL LOW-GRADE GLIOMA [NCT NCT02023905]. (11th November 2019) - Taylor, Jennie; Molinaro, Annette; Rodriguez Almaraz, Eduardo; Downey, Ciara; Phillips, Joanna; Ann Oberheim-Bush, Nancy; Butowski, Nicholas; Chang, Susan; Berger, Mitchel; Prados, Michael; Haas-Kogan, Daphne; Clarke, Jennifer
Abstract: Functional activation of the PI3K/AKT/mTOR pathway is seen in ~50% of low-grade gliomas and correlates with worse survival. Everolimus is a selective inhibitor of mTOR that targets mTOR-raptor signaling, halting proliferation and indirectly inhibiting angiogenesis. This phase 2 study evaluated the efficacy of everolimus in untreated grade II diffuse glioma. Patients were stratified by 1p19q status and PI3K pathway activation (via phosphorylation of PRAS-40) into three arms: 1) 1p19q intact, PRAS-40 phosphorylated received everolimus monotherapy; 2) 1p19q intact, PRAS-40 not phosphorylated received everolimus with temozolomide; and 3) 1p19q co-deleted received everolimus monotherapy. Primary outcome was landmark PFS-33 months for Arms 1 and 2; and PFS-38 months for Arm 3 (null hypothesis 50% for all arms individually). Key eligibility criteria included central pathology confirmation, no prior treatment, and initiation of everolimus within 120 days of most recent tissue sampling. From 05/2014 to 07/2018, 27 patients were enrolled – 16 into Arm 1; 2 into Arm 2; and 9 into Arm 3. Median age at enrollment was 38 years (range 21 – 65); median KPS 90 (range 70 – 100) and a majority were male (74%). Although follow-up is not complete, as of 05/2019 11 of 16 patients had progressed prior to 33 months in Arm 1, and 5 of 9 patients had progressed prior to 38 months in Arm 3. Toxicity was as expected with frequent grade 1/2 AEs of diarrhea, rash, and mucositis. Headache was the most common grade 3 AE and was seen in three cases. The study was closed prematurely secondary to slow accrual and loss of drug support. Updated survival data as well as results of secondary and exploratory analyses will be reported. In summary, everolimus was well tolerated in previously untreated low-grade gliomas. However, it failed to meet primary outcome of extending PFS in this population.